Pengaruh Perputaran Aktiva, Perputaran Kas, dan Loan to Deposit Ratio (LDR) terhadap Return On Asset (ROA) pada Perbankan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2013-2017 - Mahmuddin Syah Lubis; Isna Asdiani Nasution; Mery Mery; Jenvony Jenvony; Vini Yulia; Vivi Devika; Vivi Novera (Owner : Riset dan Jurnal Akuntansi, 2019)
The aim of this research is to test and analyze the effect of asset turnover, cash turnover and the Loan to Deposit Ratio (LDR) on Returns on Assets (ROA) in Banking listed on the Indonesia Stock Exchange in 2013-2017. This study uses a quantitative research approach. This type of research is descriptive research. The nature of the research conducted is a causal relationship. The population of this study was 43 banks listed on the Stock Exchange in 2013-2017 with a sample of 23 banks listed on the Indonesian Stock Exchange in 2013-2017 with 5 years of observation so that the observation samples were 115 financial statements of banking companies listed on the Indonesian Stock Exchange in 2013 -2017. The multiple regression method used in this study. The results of this study are asset turnover that has significant and significant effect on Return On Assets (ROA) in Banking listed on the Indonesia Stock Exchange in 2013-2017. Cash turnover has a significant and significant effect on Return On Assets (ROA) in Banking listed on the Indonesia Stock Exchange in 2013-2017. The Loan to Deposit Ratio (LDR) has an effect on Return On Assets (ROA) in Banking listed on the Indonesia Stock Exchange in 2013-2017. Asset turnover, cash turnover and Loan to Deposit Ratio (LDR) have an effect on and significant on Return On Assets (ROA) in Banking listed on the Indonesia Stock Exchange in 2013-2017.